Young Women’s Voices and HIV/Aids in Uganda - (:unkn) unknown (Emerald, 2010)
Introduction Despite the many studies of HIV/AIDS in Uganda and other African countries, there is little in the literature which connects directly with young women’s experiences, representations and voices (Waite and Conn, 2010, forthcoming). A research programme, on this theme, was conducted by the guest editors, and a group of British medical students, in partnership with Straight Talk Foundation (STF), Uganda. STF is a health communication NGO working with young people and communities to promote safe sex in the context of the HIV/AIDS epidemic in Uganda. STF’s experience of working with young people is that, in some Ugandan cultures and locations, young men demonstrate confidence and are vocal, yet young women remain silent and have little visibility. A starting point for the research, therefore, was recognition that young women’s voices were not being heard for the purposes of HIV prevention. The research aimed, through use of participatory methodologies (Cornwall and Jewkes, 1995), to focus strongly on young women’s voices: in this case eliciting representations of their everyday lives in the context of HIV/AIDS. Bettina Aptheker (1989, p. 39) provides a supporting rationale for the study of women’s representations of their daily lives: “If we map what we learn, connecting one meaning or invention to another, we begin to lay out a different way of seeing reality. This way of seeing is what I refer to as women’s standpoint”. Learning from women about their lives, focusing strongly on their standpoint, brings us closer to a different kind of knowledge; one that not only informs us in a different way (Harding, 1991, 2004), but also one that may have greater potential for empowerment (Parpart et al., 2002). For the purposes of HIV prevention, we argue here that exploring young women’s lives through their voices, as well as through the voices of young men, can offer a contribution to positive and empowering change.